Subordination Results Associated With Generalized Bessel Functions - Olusegun, Hamzat J. (Journal of Nepal Mathematical Society, 2019)
In the present work, subordination results for function f(z)γ belonging to a new class of analytic function Snγ (α, β, j) defined using the concept of Hadamard product are obtained. Also coeffcient estimates, growth and distortion properties for function f(z)γ in the class RSnγ (α, β, j) of Bessel type are equally investigated.